Nectins and Nectin-like Molecules in Colorectal Cancer: Role in Diagnostics, Prognostic Values, and Emerging Treatment Options: A Literature Review - Jakub Kobecki; Paweł Gajdzis; Grzegorz Mazur; Mariusz Chabowski (Diagnostics, 2022)
In 2020, colorectal cancer was the third most common type of cancer worldwide with a clearly visible increase in the number of cases each year. With relatively high mortality rates and an uncertain prognosis, colorectal cancer is a serious health problem. There is an urgent need to investigate its specific mechanism of carcinogenesis and progression in order to develop new strategies of action against this cancer. Nectins and Nectin-like molecules are cell adhesion molecules that take part in a plethora of essential processes in healthy tissues as well as mediating substantial actions for tumor initiation and evolution. Our understanding of their role and a viable application of this in anti-cancer therapy has rapidly improved in recent years. This review summarizes the current data on the role nectins and Nectin-like molecules play in colorectal cancer.